Efficient deep learning-based data-centric approach for autism spectrum disorder diagnosis from facial images using explainable AI - Alam, Mohammad Shafiul; Rashid, Muhammad Mahbubur; Faizabadi, Ahmed Rimaz; Mohd Zaki, Hasan Firdaus; Alam, Tasfiq E.; Ali, Md Shahin; Gupta, Kishor Datta; Ahsan, Md Manjurul (MDPI, 2023)
The research describes an effective deep learning-based, data-centric approach for diagnosing autism spectrum disorder from facial images. To classify ASD and non-ASD subjects, this method requires training a convolutional neural network using the facial image dataset. As a part of the data-centric approach, this research applies pre-processing and synthesizing of the training dataset. The trained model is subsequently evaluated on an independent test set in order to assess the performance matrices of various data-centric approaches. The results reveal that the proposed method that simultaneously applies the pre-processing and augmentation approach on the training dataset outperforms the recent works, achieving excellent 98.9% prediction accuracy, sensitivity, and specificity while having 99.9% AUC. This work enhances the clarity and comprehensibility of the algorithm by integrating explainable AI techniques, providing clinicians with valuable and interpretable insights into the decision-making process of the ASD diagnosis model.